Incorporation of a Non-Conventional Liana (Tetracapidium conophorum) Seed Oil Cake in Diets of Congolese Indigenous Batéké Chicks Raised Without Outdoor Access - P. P. Adzona; P. Mopoundza; A. Ngouama Dandou; J. B. Bati; M. V. Ntsoumou; H. J. Saya Ngouonomba; B. T. Bitsili; P. Akouango; H. Banga-Mboko (European Scientific Journal, ESJ, 2024)
The indigenous Batéké hen (Gallus gallus) has low productivity due to various constraints such as feeding sources. The aim of this study was to improve the productivity of the local hen using a new local protein source: Tetracarpidium conophorum meal.  A sample of ninety-six chicks 21-day old from the local population were randomized into 3 groups of 32 birds each (TC0, TC4 and TC6), with one replicate. In each group. Tetracarpidium conophorum oil cake  was incorporated into groupsTC4 (4% Tcconophorum oil cake and 11% soya oil cake), TC6 (6% T.conophorum oil cake and 9% soya oil cake) whereas TC0   served as a control group (0% T.conophorum meal and 15% soya oilcake). The experiment started at 3 weeks and lasted at 20 weeks of age. Chickens were fed ad libithum and had free access to drinkers. The results  indicated that  mortality rate  decreased (3.12 % versus 9.3),  Also, the treatment improved significantly (p ˂ 0.05)  feed intake (56.8 vs 60.1g per day), feed conversion (6.5 vs 5.7), and carcass yield (65.8 % vs 71.3 %). The final body weight at 20 weeks of age has been improved  groups (1.200g versus 1300g) .. This study indicated  that T.conophorum oil cake  may be useful in diets at 4%  thus reducing soya oil cake  from 15% to 11% of incorporation) in  a small scale poultry farming in Congo.